Trend in Energy Intensity and Carbon Performance in North Africa - Grakolet Gourene; Samia Mansour Hamouda; Zuzana Brixiova (Institute of Labor Economics (IZA), 2024)
Decoupling economic growth from environmental degradation and climate change, increasing resource efficiency, and promoting both sustainable production and sustainable lifestyles is a challenge in North Africa, a region where even a relative decoupling of income growth and carbon (CO2) emissions has not been achieved. This chapter aims to examine recent trends in emissions and the main drivers of improvement in the region's carbon intensity (carbon emissions per unit of GDP), energy intensity (energy use per unit of GDP), and per capita emissions. It also analyzes the effect of policies such as energy taxes and energy standards on the energy efficiency of SMEs in North Africa and suggests actions and policies to encourage structural transformation and ensure better energy efficiency.
Keywords: D22; G21; G32; 330; carbon emission; carbon intensity; energy intensity; inclusive growth; SMEs